Flamingo plays bingo - Punter , Russell; Semple , David (London, England, Tulsa Usborne Publishing Ltd. ; EDC Publishing, 2022)
Flamingo can't wait to play jungle bingo! But who will be crowned winner? This entertaining story for beginner readers has simple rhyming text and stylish illustrations throughout. A delight to share with very young children, or for beginner readers to read themselves, and with parent's notes on phonics at the back of the bookng skills
English stories
Keywords: Children's stories; Fiction